The value of Enterprise Resource Planning (ERP) Systems in Companies: Case study of Lesotho - Talasi, Teboho (Department of Information Systems, 2023)
While modern organisations are pressurised to invest in the latest Information Technology (IT) to keep abreast with the competitive global market, today's operational processes and supply chains also require systems that are capable of handling complex business functions. As a result, companies are investing in complex Information Systems (IS) such as Enterprise Resource Planning systems (ERPs) to cope with the dynamic business environment. Despite the continued popularity of ERPs, the literature has shown that ERP failure is a major challenge facing organisations. Findings concerning the benefits that organisations accrue from the implementation of ERPs are mixed. Nevertheless, companies invest a considerable amount of money into these systems, expecting a return on investment. The purpose of this research was to explain how ERP systems provide value to companies. An online survey strategy was used for collecting data from companies in Lesotho. The empirical results of this study confirmed a strong association between the use of ERP and ERP value, and the improvement of business processes and ERP value. This finding also emphasised the importance of organisational culture and training. The significance of this research lay in description of Lesotho context.